How Humic Acids Affect the Rheological and Transport Properties of Hydrogels - Klučáková, Martina; Smilek, Jiří; Sedláček, Petr (MDPI, 2019)
Humic acids are often regarded as substances with a supramolecular structure which plays an important role in Nature. Their addition into hydrogels can affect their behavior and functioning in different applications. This work is focused on the properties of widely-used hydrogel based on agarose after addition of humic acids–the protonated H-form of humic acids and humic acids with methylated carboxylic groups. Hydrogels enriched by humic acids were studied in terms of their viscoelastic and transport properties. Rotational rheometry and methods employing diffusion cells were used in order to describe the influence of humic acids on the properties and behavior of hydrogels. From the point of view of rheology the addition of humic acids mainly affected the loss modulus corresponding to the relaxation of hydrogel connected with its flow. In the case of diffusion experiments, the transport of dyes (methylene blue and rhodamine) and metal ions (copper and nickel) through the hydrogel was affected by interactions between humic acids and the diffusion probes. The time lag in the hydrogel enriched by humic acids was prolonged for copper, methylene blue and rhodamine. In contrast, the presence of humic acids in hydrogel slightly increased the mobility of nickel. The strongest influence of the methylation of humic acids on diffusion was observed for methylene blue.

Humic acids are often regarded as substances with a supramolecular structure which plays an important role in Nature. Their addition into hydrogels can affect their behavior and functioning in different applications. This work is focused on the properties of widely-used hydrogel based on agarose after addition of humic acids–the protonated H-form of humic acids and humic acids with methylated carboxylic groups. Hydrogels enriched by humic acids were studied in terms of their viscoelastic and transport properties. Rotational rheometry and methods employing diffusion cells were used in order to describe the influence of humic acids on the properties and behavior of hydrogels. From the point of view of rheology the addition of humic acids mainly affected the loss modulus corresponding to the relaxation of hydrogel connected with its flow. In the case of diffusion experiments, the transport of dyes (methylene blue and rhodamine) and metal ions (copper and nickel) through the hydrogel was affected by interactions between humic acids and the diffusion probes. The time lag in the hydrogel enriched by humic acids was prolonged for copper, methylene blue and rhodamine. In contrast, the presence of humic acids in hydrogel slightly increased the mobility of nickel. The strongest influence of the methylation of humic acids on diffusion was observed for methylene blue.
How Humic Acids Affect the Rheological and Transport Properties of Hydrogels
Keywords: humic acid; hydrogel; secondary structure; rheology; diffusion; humic acid; hydrogel; secondary structure; rheology; diffusion